Thermal Chondroplasty Technique for Costal Cartilage Harvesting and Contouring. Issue 3 (May 2020) - Eravci, Fakih Cihat; Ceylan, Alper; Yilmaz, Metin
Abstract : Abstract: Although costal cartilage autograft has versatile usage, harvesting the graft is an invasive procedure with potential risks for complications. Therefore, it is important to make every effort to minimize these risks. Moreover, sculpting costal cartilage to the desired shape is challenging and time-consuming because of the natural rigidity. This study aimed to evaluate cases of costal cartilage harvest in terms of the most important donor site complications and to present a novel, practical and inexpensive technique to overcome the challenges in costal cartilage harvesting and contouring. A retrospective review of patient records was made of 103 patients who underwent costal cartilage harvest by the senior author. Costal cartilage harvest was applied using either the thermal chondroplasty technique or the conventional technique on patients undergoing revision rhinoplasty surgery. The number of complications and operation times were compared between the 2 techniques. A cohort of 47 patients (30 males, 17 females; mean age 34.5 years [range, 28–48 years]) underwent costal cartilage harvest using the thermal chondroplasty technique and a cohort of 56 patients (31 males, 25 females; mean age 36 years [range, 28–52 years]) underwent costal cartilage harvest with the conventional technique. The mean operation time for the costal cartilage harvest decreased by 7.5 minutes and the total operation time decreased by 17 minutes with the use of the thermal chondroplasty technique compared to the conventional technique ( P  < 0.05). Complications of 2 pneumothorax and 1 hematoma developed in the conventional technique group, and no complications were seen in the thermal chondroplasty group. The results of this study suggest that the thermal chondroplasty technique is safer and time-saving compared to the conventional technique. Abstract : Supplemental Digital Content is available in the text